The suppression of WRKY44 by GIGANTEA-miR172 pathway is involved in drought response of Arabidopsis thaliana. - Yingying Han; Xuan Zhang; Wei Wang; Yaofeng Wang; Feng Ming (PLoS ONE)
Water availability is an important environmental factor that controls flowering time. Many plants accelerate flowering under drought conditions, a phenomenon called drought escape. Four pathways are involved in controlling flowering time, but which ones participate in drought escape is not yet known. In this study, plants with loss-of-function mutations of GIGANTEA (GI) and CONSTANS (CO) exhibited abnormal drought-escape phenotypes. The peak mRNA levels of GI and FKF1 (Flavin-binding Kelch domain F box protein 1) and the mRNA levels of CO and FT (Flowering locus T) changed under drought stress. The microRNA factor miRNA172E was up-regulated by drought stress, and its up-regulation was dependent on GI, while other miRNA172s were not. Water-loss analyses indicated that gi mutants were more sensitive while miRNA172 over-expressing (miRNA172-OX) plants were less so to drought stress than wild-type plants. Digital gene expression and real-time PCR analyses showed that WRKY44 was down-regulated by GI and miRNA172. The WRKY44 protein could interact with TOE1 (a target of miRNA172) in a yeast two-hybrid system. We proposed that GI-miRNA172-WRKY44 may regulate drought escape and drought tolerance by affecting sugar signaling in Arabidopsis.